Pinocembrin attenuates MPP+-induced neurotoxicity by the induction of heme oxygenase-1 through ERK1/2 pathway. (26th January 2016) - Wang, Hongquan; Wang, Yumin; Zhao, Linan; Cui, Qifu; Wang, Yuehua; Du, Guanhua
Highlights: Pinocembrin exerts a neuroprotective effect against MPP + -induced neurotoxicity in SH-SY5Y cells. Pinocembrin induces expression of heme oxygenase-1 through ERK1/2 pathway. Pinocembrin attenuates MPP + -induced neurotoxicity by the induction of heme oxygenase-1 expression. Abstract: Our recent study demonstrated that pinocembrin (PB), the most abundant flavonoid in propolis, has neuroprotective effect against 1-methyl-4-phenylpyridinium (MPP + )-induced SH-SY5Y neurotoxicity. However, the mechanism as how PB can induce neuroprotection is not known. In the present study, we demonstrate here that PB increased heme oxygenase-1 (HO-1) expression, which conferred protection against MPP + -induced cytotoxicity, because the inhibitor of HO-1 zinc protoporphyrin-IX attenuated the neuroprotection of PB. PB induced the phosphorylation of ERK1/2, and its cytoprotective effect was abolished by ERK1/2 inhibitors. Meanwhile, we have shown that MPP + induce the expression in a concentration-dependent manner in SH-SY5Y cells, which was further enhanced by PB. Taken together, the results suggest that PB enhances HO-1 expression to suppress MPP + -induced oxidative damage via ERK1/2 signaling pathways. These results revealed the mechanisms of PB enhances HO-1 expression, and contribute to shed some light on the mechanisms whereby PB inhibits the MPP + -induced neurotoxicity. These data indicated that PB might provide a valuable therapeutic strategy for the treatment of PD.